Mengungkap Peran Ilustrasi Musik dalam Membangun Mood, Nuansa, dan Suasana pada Film ‘Tonggak Tuo’ - Indra Syukma (Faculty of Languages and Arts, Universitas Negeri Padang, 2023)
Musical illustration plays a crucial role in establishing the mood, nuances, and atmosphere in films. This study delves into two main aspects: 1) how directors and composers apply mood, nuances, and atmosphere through musical illustration in various scenes, and 2) the significance of musical illustration in the film